2008
DOI: 10.3324/haematol.12320
|View full text |Cite
|
Sign up to set email alerts
|

Different cut-off values of quantitative D-dimer methods to predict the risk of venous thromboembolism recurrence: a post-hoc analysis of the PROLONG study

Abstract: BackgroundThe PROLONG study showed that patients with venous thromboembolism who had qualitatively abnormal results in a D-dimer assay (Clearview Simplify D-dimer) after discontinuation of vitamin K antagonism benefit from resumption of treatment with vitamin K antagonism. The objective of this study was to evaluate the possible advantage of using quantitative D-dimer assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…However, in a post-hoc analysis we have calculated specific cut-offs of different quantitative D-dimer methods on plasma samples from the PROLONG study [24]. Further studies are needed to validate these cut-offs.…”
Section: Discussionmentioning
confidence: 97%
“…However, in a post-hoc analysis we have calculated specific cut-offs of different quantitative D-dimer methods on plasma samples from the PROLONG study [24]. Further studies are needed to validate these cut-offs.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, it has been clearly demonstrated that ''normal'' DD values differ widely among different healthy and diseased populations [37]. As such, it has been suggested that each laboratory should validate the manufacturer cutoff to improve the quality of the local diagnostic pathway according to the population studied (i.e., selection of different cut-off levels according to the age or other characteristics of the patients such as renal clearance, increased fibrinogen levels and the presence of occult disease) [65]. One practical approach for harmonizing results is the use of linear regression (i.e., transformation of the method-specific regression line to a reference line common for all the assays by using a set of standard preparations containing a similar variety of cross-linked fibrin compounds), which can substantially decrease the within-methods variability (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, in a post-hoc analysis we have calculated specific cut-offs of different quantitative D-d methods on frozen plasma samples from the PROLONG study. 17 The prospective management DULCIS (D-dimer and Ultrasound in Combination Italian Study) study is currently ongoing to validate these cutoffs.…”
Section: D-dimer and Recurrent Venous Thromboembolism 485mentioning
confidence: 99%